Studies on sex expression of novel pistillate lines and their suitability for hybrid development in castor (Ricinus communis L.): Studies on sex expression of novel pistillate lines and their suitability for hybrid development in castor (Ricinus communis L.) - YAMANURA; R MOHAN KUMAR; K BHAVYA; T MANJUNATH; N NETHRA; C LAVANYA (Journal of Oilseeds Research, 2023)
Studies on sex expression of new pistillate lines and their suitability for hybrid development in castor was carried out by involving five new pistillate lines developed by ICAR-IIOR, Hyderabad along with three checks. Pistillate lines IPC-42, IPC-44 and IPC-46 observed very low number of interspersed staminate flowers (ISFs) i.e., 3.67, 5.33 and 2.33 respectively compared to checks M-574 (13.67), SKP-84 (8.33) and DPC-9 (17.33). Pistillate lines IPC-46 and IPC-44 expressed ISFs only in the quaternary order whereas they showed complete pistillateness in all other order of spikes even in the sixth order of spikes (S1T1Q1P1H1). Even under higher temperature (33.10C) and high diurnal range of temperature (13.40C) these lines expressed complete pistillateness. Hence, these female lines can be directly utilized in future breeding programme to develop high yielding potential hybrids.